2018
DOI: 10.31729/jnma.3697
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome of Vaginal Breech Delivery versus Caesarean Breech Delivery in a Tertiary Care Center

Abstract: Introduction: Breech delivery has always been matter of interest in obstetrics. Cesarean breech delivery has been preferred method of delivery. We aim to find out any differences in outcome between vaginal breech delivery and cesarean breech delivery in our setup. Methods: Data were collected from record book of Department of Gynaecology and obstetrics, Pokhara Academy of Health Sciences, Kaski, Nepal. Pregnant with breech presentation who had delivery in the centre from 2074 Baishak to 2074 chaitra were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
2
1
Order By: Relevance
“…The higher rates of perinatal morbidity and mortality associated with vaginal breech deliveries in our study are not in compliance with results from other hospitals of Nepal [ 11 13 ]. This may be because of insufficient sample size in study—that those hospitals have lower numbers of total deliveries which allows them to allocate adequate human resources for the management of those cases.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The higher rates of perinatal morbidity and mortality associated with vaginal breech deliveries in our study are not in compliance with results from other hospitals of Nepal [ 11 13 ]. This may be because of insufficient sample size in study—that those hospitals have lower numbers of total deliveries which allows them to allocate adequate human resources for the management of those cases.…”
Section: Discussioncontrasting
confidence: 85%
“…This led to many unplanned vaginal breech deliveries which in part is responsible for the high rate of adverse perinatal outcome. Nevertheless, the prevalence is not homogeneous all over the country; hospitals have reported up to 40–52% of vaginal deliveries among breech presentation with perinatal outcomes similar to or even superior to cesarean deliveries [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Apgar scores and weight at birth of neonates who were delivered by LSCS were comparatively better than those delivered vaginally. (Table 3) Similar results were demonstrated by previous studies conducted in Nepal 10,20 and India. 7 .…”
Section: Discussionsupporting
confidence: 90%
“…10 Similarly, Choudhary et al reported maximum breech (70.6%) in age-group 20-30 years. 11 In the present study, approximately 64.4% were primigravida and 35.6% were multigravida. In similar studies, Panda et al, Kavita et al and Sonali et al, reported 52%, 62% and 53% primigravida.…”
Section: Discussionsupporting
confidence: 43%